A retrospective analysis of vortioxetine utilization in children and adolescents with major depressive disorder in clinical practice - Xianmei Luo; Shu Yu; Keliang Pan; Lin Cheng; Fan Luo; Handi Zhang; Mingjun Duan; Yajun Zhang (BMC Psychiatry)
Abstract Background Treating depression in children and adolescents has always been a challenge in clinical pharmacotherapy. Vortioxetine, as a new type of antidepressant, is considered to have the potential for use in the treatment of depression in children and adolescents. This study aimed to evaluate the usage of vortioxetine and its efficacy and tolerability in children and adolescents with major depressive disorder in a real-world study. Methods A retrospective survey of vortioxetine treatment was conducted at a Class A tertiary mental health hospital. Data regarding the demographic and clinical characteristics were collected among children and adolescents with major depressive disorder from electronic medical record system. Results The study included a total of 253 depressive patients, comprising 96 males and 157 females, who were prescribed vortioxetine at any time during the research period. One hundred and twenty-three patients (43.62%) received vortioxetine treatment at the initial visit. Of the total patients, 27 (10.67%) reported side effect, such as nausea, vomiting, dizziness, palpitations, diarrhea, drowsiness, and itching. Additionally, 20 (7.91%) discontinued medical treatment due to adverse effect. No significant difference was found between males and females in drug-related adverse events (X2 = 0.56, P = 0.454). Furthermore, 96 (37.94%) reported relief from their symptoms in all patients, with a significant difference observed between males and females in reporting symptom relief (X2 = 3.934, P = 0.047). But this difference disappeared in patients who took vortioxetine alone and those who took it for more than three months. Conclusion There exists a certain proportion of children and adolescents suffering from depression who are prescribed vortioxetine in an off-label manner in psychiatric clinics. Vortioxetine demonstrates well tolerability in clinical practice. However, the proportion of self-report symptom alleviation is comparatively unsatisfactory. Furthermore, gender appears influence on self-report symptom relief.